Integrating sensing elements on external fixators for healing assessment of fractured femur. Issue 12 (11th February 2016) - Ong, W. H.; Chiu, W. K.; Russ, M.; Chiu, Z. K.
Summary: This paper highlights the potential of integrating SHM concepts into an external fixator with the aim of using it to assess the healing of a fractured femur. A finite element analysis was first performed on the fixated femur to understand the response of the fixated femur in its fractured and healed state. The underlying mechanics will be used to establish a suitable monitoring strategy for assessment of healing. The results will be supported by a series of experiments using a fixated saw‐bone femur, which has been cut to simulate fracture. The cut was filled with epoxy, and the curing of this epoxy was used to simulate healing of the fractured region. The findings lead to an actuation and sensing protocol able to determine the state of union of a fixated long bone. This methodology was tested further by using modelling clay to approximate the mass added by soft tissue surrounding the bone. These results illustrate that the integration of SHM and orthopaedic concepts can provide a quantitative measure that can be used in conjunction with existing techniques for the monitoring of the state of healing of the fracture. This represents a significant potential of reducing or eliminating the qualitative healing assessment. Copyright © 2016 John Wiley & Sons, Ltd.